2019
DOI: 10.1109/tste.2018.2849318
|View full text |Cite
|
Sign up to set email alerts
|

Joint Optimization of Operation and Maintenance Policies for Solar-Powered Microgrids

Abstract: received the Ph.D. degree in reliability engineering and asset management from the University of Cambridge, U.K., in 2016. Currently, he is a research associate at the Distributed Information and Automation Laboratory at the University of Cambridge. His research interests include stochastic process, predictive maintenance, maintenance optimization and reliability of power equipment. Ajith Kumar Parlikad received the Ph.D. degree in manufacturing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…We represent the microgrid purchased power from the main grid and sold power to the main grid with y gp,ω m,t,h , and y gs,ω m,t,h , respectively. Purchasing and selling limits, F gp m and F gs m , are enforced through constraint (16). MMG in locally connected mode can be modeled by setting g p,ω m,t,h and g s,ω m,t,h to zero.…”
Section: B Adaptive Predictive Operations and Maintenance Of Mmgmentioning
confidence: 99%
See 2 more Smart Citations
“…We represent the microgrid purchased power from the main grid and sold power to the main grid with y gp,ω m,t,h , and y gs,ω m,t,h , respectively. Purchasing and selling limits, F gp m and F gs m , are enforced through constraint (16). MMG in locally connected mode can be modeled by setting g p,ω m,t,h and g s,ω m,t,h to zero.…”
Section: B Adaptive Predictive Operations and Maintenance Of Mmgmentioning
confidence: 99%
“…These risk predictions rely on condition monitoring techniques that monitor indicators of asset degradation from raw sensor inputs, such as vibration, temperature, and performance [14], [15]. Condition monitoring systems are actively used in wind turbines (WT), photovoltaics (PV), and conventional generators [16]- [19]. For a comprehensive review of condition monitoring methods in power generation, readers are referred to [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that PM policy performs best when the utilization time (horizon) is long. A grid-connected solar PV system maintenance optimization policy was reported by [26]. The authors developed the maintenance cost minimization optimization, based on a twolayered approach, by first calculating the aging cost penalty, which was subsequently used as an input to calculate the optimal maintenance cost.…”
Section: Introductionmentioning
confidence: 99%
“…Microgrids, based on the needs of local network, can be operated in either grid-connected mode or islanded mode. They are seen to be increasingly important to achieve a reliable, flexible, and sustainable electricity network [7]. Every microgrid can include different electrical and thermal assets such as CHP systems, natural gas or diesel generators, PV systems with or without battery storage systems [8], boilers and chillers, etc.…”
Section: Introductionmentioning
confidence: 99%